THE INFLUENCE OF ORGANIZATIONAL CULTURE AND WORK MOTIVATION ON EMPLOYEE JOB SATISFACTION: A STUDY AT PT TELEKOMUNIKASI SELULER REGION SUMBAGUT - Nur Hasanah Azka Tiffany; Iskandarini; Vivi Gusrini Pohan (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2024)
This study aims to analyze the influence of organizational culture and work motivation on employee job satisfaction at PT Telekomunikasi Seluler Region Sumbagut. The background of this research underscores the importance of understanding and enhancing organizational culture and work motivation to improve employee job satisfaction, particularly in telecommunication companies operating in a highly competitive and dynamic business environment. Organizational culture is measured through dimensions such as agility, customer centricity, innovation, open mindset, networking, and meritocracy, while work motivation is measured using Alderfer's ERG Theory, which includes the dimensions of existence, relatedness, and growth. Employee job satisfaction is measured using psychological, social, physical, and financial dimensions. The research method employed is a quantitative approach with multiple linear regression analysis. The sampling technique used is saturated sampling, with respondents comprising all employees of PT Telekomunikasi Seluler Region Sumbagut. Data collection was conducted through questionnaires that have been tested for validity and reliability. Data analysis includes normality tests, multicollinearity tests, F-tests, t-tests, and the determination coefficient (R-Square). The results show that organizational culture and work motivation have a positive and significant impact on employee job satisfaction. These two variables simultaneously contribute significantly to the improvement of employee job satisfaction, emphasizing that effective management of organizational culture and appropriate motivational strategies are key to enhancing employee job satisfaction.